Equivalent Solution Method for the Analytical Transverse Modal Shape of Hollow Slab Bridges - Chunxu Qu; Yachao Gong; Liang Ren; Rui Zhang; Hongnan Li (Mathematics, 2022)
Hollow slab bridges are the most widely used form of small- and medium-span bridges. The existing research on the dynamic characteristics of hollow slab bridges is mostly based on numerical models, but there is a lack of theoretical analyses of their dynamic characteristics. In this paper, the relationship between the dynamic characteristic parameters and structural parameters of a hollow slab bridge is explored theoretically. Firstly, the solid model of a hollow slab bridge was established, and a modal analysis was carried out on it as a reference. Then, an orthotropic plate was used as an equivalent dynamic analysis model, and the analytical form of the transverse modal shape was deduced based on Kirchhoff thin plate theory. Furthermore, one hinge joint was considered as being equivalent to the elastic support boundary, and the local structure and the equivalent elastic support boundary were used to reflect the transverse modal shape of the original structure. The analysis shows that the influence of hinge joints on the transverse modal shape is mainly reflected in the transmission of bending deformation. Through comparison and verification, the results show that the analytical expression of the transverse modal shape can well describe the low-order transverse modal shape of a hollow slab bridge.